Experimental Study on Retrofitted RC Beams with Externally Bonded SIFCON Laminates (International Journal of Advanced Research in Science, Management and Technology, 2017)
This paper presents the results of experimental Studies concerning the flexural strengthening of RC beam using externally bonded Slurry Infiltrated Fibrous Concrete (SIFCON) Laminates. Now days it is common observation that structures are unable to offer service as much as they are expected as per design. This is often as a result of deterioration of the concrete and reinforcements caused by environmental factors The Retrofitting will be used as an cost-effective solution to the replacement of these structures and is commonly the sole feasible option.   Slurry Infiltrated Fiber Concrete (SIFCON) are well suited to the current application as a result of their high strength-to-weight ratio, good fatigue properties, and wonderful resistance to corrosion. This study presents a method for retrofitting of reinforced concrete beams to enhance the actual load carrying capacity using High Performance fibre Reinforced Cementitious Composites (HPFRCCs) laminates SIFCON and which are directly bonded to the tension face at the soffit of the beam by epoxy adhesives and are tested under compression cyclic loading. In this experimental study, A total of Six beams of size 150 mm width × 230 mm depth × 1650 mm length and four  SIFCON laminates of size 150 mm width × 25 mm depth × 1550 mm length  are casted and tested in the laboratory. The SIFCON laminates are bonded in between the beam supports. Four beams were retrofitted with SIFCON laminates (RBSF1,RBSF2,RBSF3,RBSF4) and remaining two beams were tested under compression loading (CB1 and CB2) and checked up to failure. Static responses of all the beams were evaluated in terms of strength, ductility ratio, stiffness ratio, compositeness between laminate and concrete, and the associated failure modes. Comparison was made between the Control specimen and Strengthened beams.. The results show that the strengthened beams exhibit increased flexural strength, enhanced flexural stiffness, and composite action until failure.
Keywords: Slurry Infiltrated Fibrous Concrete, High Performance fibre Reinforced Cementitious Composites, RBSF1,RBSF2,RBSF3,RBSF4, CB1 and CB2.